Nonsurgical Rhinoplasty: A Graft-based Technique - Francesco Segreto, MD; Giovanni Francesco Marangi, MD, PhD; Vincenzo Cerbone, MD; Mario Alessandri-Bonetti, MD; Erika Caldaria, MS; Paolo Persichetti, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2019)
Background:. Nonsurgical rhinoplasty with hyaluronic acid (HA) has gained popularity due to its efficacy and minimal downtime. From a structural standpoint, it is like performing a tridimensional reshaping where only enhancement by grafts is allowed. To date, indications, technique, and products are still debated. The aim of this study is to describe the author’s experience with nonsurgical nasal reshaping, focusing on the indications and maneuvers to safely achieve, by mean of HA, the grafts previously described for surgical rhinoplasty. Materials and Methods:. A total of 70 consecutive patients underwent nonsurgical rhinoplasty using the same type of HA. The rhinoplasty module of FACE-Q was administered to all patients before treatment and 15 days posttreatment. Statistical analysis was performed. Results:. No complication was experienced. Two (2.8%) patients required a retouch after 15 days for further dorsal correction. There was a statistically significant difference between preoperative and postoperative values in all domains and overall scores of the rhinoplasty module of FACE-Q. Conclusions:. The graft-based technique proved to be safe, effective, and reliable. It may allow correction of selected nasal defects with reduced cost and minimal downtime.